2006
DOI: 10.1021/bi061531o
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Interaction of the Double-Stranded RNA (dsRNA) Binding Domain of Protein Kinase R with Short dsRNA Sequences

Abstract: The dsRNA-activated protein kinase (PKR) plays a major role in the cellular response to viral infection. PKR contains an N-terminal dsRNA binding domain (dsRBD) and a C-terminal kinase domain. The dsRBD consists of two tandem copies of a conserved double-stranded RNA binding motif, dsRBM1 and dsRBM2. dsRNA binding is believed to activate PKR by inducing dimerization and subsequent autophosphorylation reactions. We have characterized the function of the dsRBD by assessing the binding of dsRBM1 and dsRBD to a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
83
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(93 citation statements)
references
References 60 publications
10
83
0
Order By: Relevance
“…These findings are consistent with reports of other dsRBD-containing proteins involved in small RNA pathways. For example, dsRBDs of both HYL1 (HYPONASTIC LEAVES 1) and PKR that exhibit noncanonical binding and extensive line broadening have been shown to bind RNA without apparent specificity (55,65,66). Similarly, we have been unable to detect by NMR nucleotide-specific changes to RNA targets complexed with DGCR8 core .…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…These findings are consistent with reports of other dsRBD-containing proteins involved in small RNA pathways. For example, dsRBDs of both HYL1 (HYPONASTIC LEAVES 1) and PKR that exhibit noncanonical binding and extensive line broadening have been shown to bind RNA without apparent specificity (55,65,66). Similarly, we have been unable to detect by NMR nucleotide-specific changes to RNA targets complexed with DGCR8 core .…”
Section: Discussionmentioning
confidence: 67%
“…Analogous to the protein spectra, pri-mir-16 imino-proton peaks were broadened globally and severely. This result suggests that DGCR8 dsRBDs simultaneously bind overlapping interfaces of the RNA in a manner resembling nonspecific PKR⅐dsRNA complex formation (66). Finally, the Dicer accessory dsRBD-containing protein-transactivating response RNA-binding protein and two homologs, including PKR, were most recently shown to diffuse along dsRNA substrates, which is clearly an activity conceivably adopted by DGCR8 to anchor Drosha-DGCR8 heterodimers (67).…”
Section: Discussionmentioning
confidence: 94%
“…30;32 NMR mapping experiments indicated that dsRBM1 plays the dominant role in dsRBD binding to short dsRNAs. 30 Three dsRBD bind to the 20 bp dsRNA in 75 mM NaCl with K d s of 11, 210, and 780 nM. 32 Thus, the affinities of PKR and dsRBD are similar, suggesting a similar binding interface, but the presence of the kinase domain and linker region results in steric hindrance which prevents a third PKR from binding and increases the minimal overlap.…”
Section: Discussionmentioning
confidence: 99%
“…For example, circular dichroism (CD) spectroscopy is a technique that is commonly used to assess the secondary-structural features of chiral biomolecules (18), and was used to validate the bending hypothesis derived from the Xlrbpa2-dsRNA crystal structure (14). For protein-nucleic acid interactions in general, an experimental paradigm has been established whereby changes in the nucleic acid ellipticity serve as the source of signal, because ellipticity is inversely proportional to the winding angle of the helix (19). This mechanism has been leveraged as a source of signal in experiments that aimed to determine the saturating stoichiometry of the dsRBD-dsRNA interaction, yielding stoichiometries in good agreement with those determined by orthogonal techniques such as analytical ultracentrifugation (19).…”
Section: Introductionmentioning
confidence: 99%
“…For protein-nucleic acid interactions in general, an experimental paradigm has been established whereby changes in the nucleic acid ellipticity serve as the source of signal, because ellipticity is inversely proportional to the winding angle of the helix (19). This mechanism has been leveraged as a source of signal in experiments that aimed to determine the saturating stoichiometry of the dsRBD-dsRNA interaction, yielding stoichiometries in good agreement with those determined by orthogonal techniques such as analytical ultracentrifugation (19). Indeed, in a previous study employing a similar CD experiment (7), we also reported the stoichiometry of TRBP binding to dsRNAs of various lengths ( Fig.…”
Section: Introductionmentioning
confidence: 99%